2019
DOI: 10.1007/s11258-019-00954-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of gall formation in relation to chemotype distribution in Thymus vulgaris

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Nature B.V.. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Importantly, several studies have shown patterns in distribution of plant chemotypes across spatial and abiotic gradients. For instance, in T. vulgaris it has been found that the composition of secondary compounds differs significantly between sites in the south of France, and has been shown to depend on soil composition, winter ambient temperatures (Thompson et al 2007(Thompson et al , 2019, and chemotypic differences are associated with herbivory (Linhart et al 1999). Furthermore, chemotype frequency of Pinus banksiana plants in the US was observed to be correlated with abiotic factors, such as precipitation (Taft et al 2015).…”
Section: Geographic Distribution Of Terpenoid Chemotypes In Tanacetum...mentioning
confidence: 99%
“…Importantly, several studies have shown patterns in distribution of plant chemotypes across spatial and abiotic gradients. For instance, in T. vulgaris it has been found that the composition of secondary compounds differs significantly between sites in the south of France, and has been shown to depend on soil composition, winter ambient temperatures (Thompson et al 2007(Thompson et al , 2019, and chemotypic differences are associated with herbivory (Linhart et al 1999). Furthermore, chemotype frequency of Pinus banksiana plants in the US was observed to be correlated with abiotic factors, such as precipitation (Taft et al 2015).…”
Section: Geographic Distribution Of Terpenoid Chemotypes In Tanacetum...mentioning
confidence: 99%
“…Quantitative and qualitative variation may play an important role in defining the ecological niche of plants. Several authors show the implications of terpenes in many ecological processes such as pollinator attraction [30], host-parasite interaction [31], or tolerance to abiotic stresses [32,33]. However, the mechanisms of action remain to be discovered and the demonstration of the adaptive advantages of one compound is still a challenge for ecologists.…”
Section: Discussionmentioning
confidence: 99%